SSI-Federation: facilitating identity federation using self sovereign identity for Web-services - Mahir, Sajid Imam; Ahsan, Navid Alvi; Eshan, Md. Mehrab Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.